COVID-19 VACCINE DRIVERS: AN INTEGRATIVE REVIEW - Eduarda Almeida de Souza, Cicera; Laura do Amparo Delfino, Maria; Juli Matias da Silva, Jennifer; Thiago Paiva Monte, Francisco; Rodrigues da Cruz, Rosana; Caroline Vasques Dantas Coelho, Ananda; de Fatima Souza Capelario, Elenice; Carvalho Felix, Sarah; Guilherme Pereira da Silva Marques, Victor; Gomes Venceslau, Hemanuelle (Health and Society, 2022)
Introduction: Faced with the rapid spread of COVID-19 on all continents, on January 30, 2020 the World Health Organization (WHO) declared the novel coronavirus outbreak (classified as SARS-CoV-2) a public health emergency. of international interest, the highest level of alarm. Among the recommendations were the acceleration of vaccines, therapeutic and diagnostic measures. Objective: To identify in the literature the challenges faced in the vaccination process. Methodology: The study is an integrative literature review of a descriptive-exploratory nature, carried out in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature on Health Sciences (LILACS), Banco Regional Data on Health Technology Assessment Reports of the Americas (BRISA), Nursing Database (BDENF), and Bibliographic Index Español en Ciencias de la Salud (IBECS). Results and Discussions: The challenges of equitable access to vaccination against COVID-19 are enormous, ranging from the production of sufficient doses to the organization of efficient vaccination programs, including ensuring a distribution that meets ethical and epidemiological criteria. . At the global level, unless governments in high-income countries and the pharmaceutical industry change their behavior and take urgent measures to ensure that sufficient doses of the COVID-19 vaccine are produced and equitably distributed, there will be no ethics and justice in relationships. between peoples, nor will there be effective control of the pandemic. Conclusion: this integrative review showed, through the scientific literature, the importance of vaccination, especially with the emergence of variants. Therefore, international coordination and cooperation between researchers and health professionals is essential to guarantee mass vaccination.